An Assessment of the Liability of Electricity suppliers under Cameroonian Law (African Journal of Law and Politics, 2025)
Electricity access in Cameroon is about 65-88% in urban areas and about 14% in rural areas. However,the product or service may still reach the final consumer but does not conform to quality, sample,specification, merchantability and fitness for purpose. There is no doubt that consumers in Cameroonelectricity sector are protected by a superfluity of laws though most consumers are not conscious oraware and, in most cases, they shy away due to litigational bottlenecks. Nevertheless, establishingliability of electricity suppliers under Cameroonian law can be seen from the civil perspective and evenwithin the domain of criminal law. This paper therefore probs into assessing the liability of electricitysuppliers and the quality of electricity services under Cameroonian Law. It is therefore ascertained thatthough there exist patchwork of laws in this sector, consumers still remain vulnerable. Somerecommendations are made to move beyond many failures inter alia; strong competition, responsibleconsumer attitude and a favorable and enabling environment to seek court redress.